Controlling Inflammation Pre-Emptively or at the Time of Cutaneous Injury Optimises Outcome of Skin Scarring - Ud-Din, Sara; Bayat, Ardeshir (Frontiers in Immunology, 2022)
Inflammation plays an active role during the wound healing process. There is a direct association between the extent of injury as well as inflammation and the amount of subsequent cutaneous scarring. Evidence to date demonstrates that high levels of inflammation are associated with excessive dermal scarring and formation of abnormal pathological scars such as keloids and hypertrophic scars. In view of the multiple important cell types being involved in the inflammatory process and their influence on the extent of scar formation, many scar therapies should aim to target these cells in order to control inflammation and by association help improve scar outcome. However, most current treatment strategies for the management of a newly formed skin scar often adopt a watch-and-wait approach prior to commencing targeted anti-inflammatory therapy. Most of these therapies are evaluated in the remodelling-phase of wound-healing and the evaluation of anti-inflammatory treatments at earlier stages of healing have not been fully explored and remain limited. Taken together, in order to minimise the risk of developing a poor scar outcome, taking an early intervention prior to skin injury would be optimal, however, the concept of pre-emptively priming the skin prior to injury has not yet been thoroughly evaluated. Therefore, the aim of this review was to evaluate scar therapies that aim to target inflammation prior to a scar forming or immediately after injury, with a focus on the role of pre-emptive priming of skin prior to injury in order to control inflammation for the prevention of poor scarring outcome.